New developments in the coordination chemistry of Gold(I), Gold(II) and Gold(III) with C-, N- , P-and S-donor ligands - Coetzee, Jacorien (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2007.